2016
DOI: 10.1093/humrep/dew142
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation analysis detects novel candidate genes involved in follicular growth and oocyte maturation in a cohort of premature ovarian failure cases

Abstract: STUDY QUESTIONCan spontaneous premature ovarian failure (POF) patients derived from population-based biobanks reveal the association between copy number variations (CNVs) and POF?SUMMARY ANSWERCNVs can hamper the functional capacity of ovaries by disrupting key genes and pathways essential for proper ovarian function.WHAT IS KNOWN ALREADYPOF is defined as the cessation of ovarian function before the age of 40 years. POF is a major reason for female infertility, although its cause remains largely unknown.STUDY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 72 publications
3
39
0
4
Order By: Relevance
“…Herein, POI-7 has a microduplication (11.4-kb) in this gene ( Table 2 ). Furthermore, an 83.8-kb deletion in the CPBE1 gene was found in POI-14 ( Table 2 ), the same region previously identified in some POI cohorts [ 12 , 14 , 15 ]. In addition, the rare and deleterious heterozygous missense variant in CPEB1 (c.259C>T;p.Arg87Cys) was also identified in POI-4 ( Table 2 ).…”
Section: Discussionsupporting
confidence: 65%
“…Herein, POI-7 has a microduplication (11.4-kb) in this gene ( Table 2 ). Furthermore, an 83.8-kb deletion in the CPBE1 gene was found in POI-14 ( Table 2 ), the same region previously identified in some POI cohorts [ 12 , 14 , 15 ]. In addition, the rare and deleterious heterozygous missense variant in CPEB1 (c.259C>T;p.Arg87Cys) was also identified in POI-4 ( Table 2 ).…”
Section: Discussionsupporting
confidence: 65%
“…In addition, abnormalities in Gdf9 and BMP15 expression are associated with polycystic ovarian syndrome (PCOS) and primary ovarian insufficiency (POI) in humans [4850]. The receptor Scarb1 was differentially expressed in DDT lineage granulosa and has been associated with POI [51]. The growth factor IGF1 and the receptors Pdgfra and Ghr were also differentially expressed in the DDT lineage and have been implicated in PCOS [5254].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence in mice has identified the ontogeny of the expression patterns of this protein, which suggests it has a role in the primordial to primary transitioncontributing to transcription status of the follicle (Schultz et al 2018). However, studies in human POI cohorts reveal conflicting data, with overexpression observed in some cases, and other studies contend that TBPs do not contribute to POI (Tsuiko et al 2016. A new potential marker of primordial follicles about to undergo activation is the expression status of keratin.…”
Section: Current Research Into Primordial Follicle Activationmentioning
confidence: 99%